Verification of Okun’s Law on Russian Data - Yu. K. Zaitsev (Финансы: теория и практика, 2022)
The purpose of the study is to assess the empirical relationship between economic growth and unemployment in the Russian economy. The research methodology is based on an econometric analysis of time series representing data on unemployment and economic growth to identify an empirical relationship between these variables. In the article continued the work on identifying the relationship between the unemployment rate and GDP in Russia based on empirical data. Based on the results of the optimal length model, the long-term Okun coefficient describing the relationship between GDP and unemployment is calculated. As a result of the empirical assessment, the Okun coefficient was obtained equal to 0.87, which is consistent with previous studies based on the data of the Russian economy. The discrepancies can be explained by the pandemic factor in 2020. It is concluded that the value of the long-term Okun coefficient confirms the stable relationship between GDP and the unemployment rate. However, its value for Russia is somewhat inferior to estimates for most developed countries and is comparable to indicators for emerging market countries. The results of the study can be used in the construction of short-term forecasts of the response of unemployment to changes in GDP, as well as in the development of macroeconomic policy measures in Russia as a whole.